Bulk modulus of CaO under high pressure up to 65 GPa - DAOUD, Salah; Rekab-Djabri, Hamza (International Journal of Advanced Chemistry, 2022)
In the present study we used some equilibrium experimental data reported by Mammon et al. (Geophysical Research Letters, Vol. 8, No. 2, pp. 140-142) to investigate the effect of high pressure up to 65 GPa on the bulk modulus of calcium oxide (CaO) material. We used the Vinet’s equation of state (EOS) model. The fit of the bulk modulus as a function of pressure p obeys the 2nd order polynomial expression: B = 115.37 + 3.84 p - 7.25 x 10-3 p2 (where both B and p are expressed in GPa). Our results are analyzed and compared with other theoretical data of the literature. Similar behavior for the bulk modulus versus pressure was observed for some other materials with different crystallographic structures from the literature, which commonly increases with increasing pressure.We estimate also the Debye temperature θD of our material of interest using the experiential lattice parameter and elastic constants measured at normal conditions by Speziale et al. (Journal of Geophysical Research, Vol. 111, (2006), pp. B02203 (12 pages)). Our obtained value (670.1 K) is in good agreement with other data of the literature.